Literature and Spanish as a foreign language: the matter of otherness - Antônio Andrade (Gragoatá, 2008)
We know that many theoretical references not only demonstrate the importance of otherness in the studies of culture, philosophy, art, and literature, but also point toward a path to which the debate around the Spanish as a foreign language is leading its researchers. It seems that the basic issue for all scholars of Spanish as a foreign language in Brazil is to think about what cultural and linguistic aspects are involved in the teachinglearning process of a language which is situated between the proximity and differentiation. Therefore, this paper will attempt to draw a relationship between literary studies and theoretical field of Applied Linguistics to the teaching of Spanish as a foreign language, making use of the theoretical question of otherness and discussing their productivity for both areas of reflection – language and literature –, constituents of academic training of professionals with qualification in Spanish and Portuguese.